(untitled) (Journal of Science and Technology, 2016)
This work investigates the effect of waste plastics (high density polyethylene (HDPE)) addition on the production of premium grade iron nuggets from iron oxide using metallurgical coke as reducing agent. Composite pellets were formed from mixtures of iron oxide and carbonaceous materials consisting of coke, HDPE and three blends of coke-HDPE. The iron oxidecarbonaceous material composites were heated very rapidly in a laboratory scale horizontal tube furnace at 1500°C in a continuous stream of argon and the off gas was analysed continuously using an online infrared gas analyser and a gas chromatographic analyser. Elemental analyses of samples of the reduced metal were performed chemically for its carbon content and the extent of reduction was calculated based on a mass balance for removable oxygen. The results indicate that blending of coke with HDPE has the beneficial effect of improving the extent of reduction of iron oxide, with the time for complete reduction improving significantly from 600s (Coke) to 330s for Blends 1 and 2. Blending of coke with HDPE led to over 20% reduction in direct carbon dioxide emissions.